Determinants of Key Audit Matters Disclosure: Evidence from Indonesia - Pertiwi Khoerunnissa, Gina; Dian Indira Kusuma, Poppy; Jannah, Miftakhul (Riset Akuntansi dan Keuangan Indonesia, 2025)
This study aims to examine the determinants of key audit matters (KAM) disclosure in Indonesia. The sample consists of 951 companies listed on the IDX during 2022-2024. Data from 1,770 audit reports were analyzed using multiple regression analysis. The results show that audit fees and corporate governance have a positive relationship with key audit matters disclosure. However, this study fails to prove the positive relation between Big 4 auditors and key audit matters disclosure, as well as between female auditors and key audit matters disclosure. Meanwhile, the audit technology is proven to have a negative relationship with key audit matters disclosure. These results imply the importance of determining appropriate audit fees and the significance of having effective corporate governance in place.